2019
DOI: 10.1182/blood-2019-130487
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Effects of Crizotinib in Human Acute Myeloid Leukemia with TP53 Alterations

Abstract: Introduction: In acute myeloid leukemia (AML) standard therapies induce complete remission in 50-70% of patients, but overall two-year survival is less than 20-30% because of high relapse rates. AML with TP53 alteration is largely insensitive to chemotherapy, modern targeted agents, and hematopoietic stem cell transplantation. Mutations in TP53 are seen in approximately 20% of AML and confer a particularly poor prognosis decreasing the 1-2 year survival rates to 0-10%. Leukemia stem cells (LSCs) are defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has not been enrolled in clinical trials for AML. Nevertheless, it has been used in studies of high-risk AML patients, with TP53 Mut and obtained very promising results ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been enrolled in clinical trials for AML. Nevertheless, it has been used in studies of high-risk AML patients, with TP53 Mut and obtained very promising results ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…It also includes patients who have TP53 Mut genotype, which are biomarkers associated with poor prognosis ( 14 ). MOM recommends treating these patients with Crizotinib, a drug used in other studies with TP53 Mut AML patients which in fact showed very promising results ( 34 ). In addition, this subgroup shows a deficiency in amino acid metabolism which may lead to alternative treatment therapies based on metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…It also includes patients who have TP53 Mut genotype, which are biomarkers associated with poor prognosis [134]. MOM recommends treating these patients with Crizotinib, a drug used in other studies with TP53 Mut AML patients which in fact showed very promising results [107]. In addition, this subgroup shows a deficiency in amino acid metabolism which may lead to alternative treatment therapies based on metabolomics.…”
Section: Discussion Of Sectionmentioning
confidence: 99%
“…It has not been enrolled in clinical trials for AML. Nevertheless, it has been used in studies of high-risk AML patients, with TP53 Mut and obtained very promising results [107].…”
Section: Flt3 Cbf-myh11 and Nras Variants Play A Key Role In Acute M...mentioning
confidence: 99%